The concept of justice in comparative perspective / A.S.W. Kakembo - A. S. W, Kakembo (1995)
The concept of justice is about the consideration of parallel issues, concerns, needs,deserts and entitlements of people and worlds in various circumstances. And the significance of justice is to ensure that there is a justly balanced order of things and the way entitlements, needs, deserts, merit and burdens are distributed across time, peoples and worlds. This involves a conflict, and the consideration of such conflict, is what calls for theories of justice.